Level of Precompetitive Anxiety and Self-Confidence in High Level Padel Players - Castillo-Rodriguez, Alfonso; Hernández-Mendo, Antonio; Alvero-Cruz, José Ramón; Onetti-Onetti, Wanesa; Fernández-García, José Carlos (Frontiers in Psychology, 2022)
The objectives of the present study were firstly to evaluate precompetitive anxiety and self-confidence (SC) in paddle-tennis players according to their playing level; and secondly, to study the factors that influence the levels of precompetitive anxiety and SC. One hundred paddle-tennis players, all of whom were federated men (age: M = 27.6, SD = 7.5 years; weight: M = 73.4, SD = 9.8kg; height: M = 175.6; SD = 7.5cm) participated in the research. The CSAI-2 (Competitive State Anxiety Inventory-2) questionnaire was used and a one-way ANOVA and a two- and three-ways MANOVA were conducted. The results show that the players from a better category had higher scores in SC and lower scores in somatic anxiety (SA) (η2=0.10 and η2=0.12, respectively). Moreover, the factors of category, body mass index (BMI) and experience, predicted 82% of the variance explained by the SC of the player. As a conclusion, this study has made it possible to ascertain that the playing category, understood as the level of the paddle-tennis players, determines the levels of anxiety and SC and represents a key factor for the prediction of sports performance.